Manusia Dalam Logika Politik di Era Media Digital - Prasetyono, Emanuel; Pandor, Pius (Studia Philosophica et Theologica, 2024)
Political praxis in the digital media era often contains biases in understanding human dignity. This article wants to investigate whether the political logic in such an era contains certain concepts about humans that are implicit, hidden, or intentionally hidden. The theoretical framework of Shoshana Zuboff and Agus Sudibyo's thoughts on "Capital Surveillance" and "Digital Universe" is the reference used by the author to see to what extent the role of the use of digital technology and virtual spaces in political propaganda contains humanitarian biases and does not direct political goals on human dignity. The results of the author's observations and research show that political praxis in the digital media era has utilized humanitarian issues only for the sake of pragmatic and transactional electoral political interests. The author finds that human dignity in political practice in the digital media era is only an instrument, not a goal.